Anthologizing Canadian Literature : Theoretical and Cultural Perspectives - Lecker, Robert, 1951- (Book collections on Project MUSE., 2016)
Uncovers archetypal imagery in Dostoevsky s stories and novels and argues that archetypes bring a new dimension to our appreciation and understanding of his works. Selected texts are analyzed in the light of fresh research in Dostoevsky studies, cultural history, comparative mythology, and depth psychology.